Umgalelo and the failure of the church? : a study in voluntary associations in Mbekweni Paarl - Kokoali, Christian Tumelo (Department of Religious Studies, 2024)
Umgalelo are defined as "small-scale informal mutual benefit societies". The name is derived from the Xhosa verb ukugalela, "to pour forth, out, or in". In the old Xhosa- tradition it could be used as ukugatela iinkomo, to pour in cattle in competing for a wife. Two or more contestants for a wife would bid against each other with cattle, one beating the other by a higher price. Nowadays umgalelo refers associations which involve the "pouring mutual benefit and good fellowship. to the voluntary in" of money for In Zulu these associations are called maholisana from ukukhola, to pay. In Southern Sotho the name is 'ho amohedisana', literally meaning to make each other receive from the verb amhoela, 'to receive. This system of umgalelo began with the establishment of money economy among Africans in the gold and diamond mines at the end of the nineteenth century.